The rock mechanics and acoustic emission characteristics of rock salt under tension-compression alternating. Issue 5 (September 2019) - Liu, Jianfeng; Liao, Yilin; Deng, Chaofu; Zhang, Qiangxing; Li, Zhicheng; Zeng, Yin
Abstract: In order to study the stress state and acoustic emission characteristics of salt rock energy storage during high frequency injection and production of compressed. the self-developed spring specimen limit tension and compression cycle test rock specimen fixing device based on the MTS815 Flex Test GT rock mechanics test system and acoustic emission (AE) three-dimensional positioning real-time monitoring system was used to study on mechanical characteristics and AE characteristics of pure salt rock and impurity salt rock under tension-compression alternating tests for the first time. The test results show that: (1) Under the stress path of tension-compression alternating, the tensile strength of pure salt rock is 0.95 MPa, impurity salt rock tensile strength increased by 47.37% compared with pure salt rock, axial deformation of impurity salt rock is 0.25mm, while pure salt rock is 1.40 times of it. (2) During the compression stage, AE signals with uniform distribution are produced by the effect of mutual dislocation, slip and micro-defect closure in salt rock, which has a certain end-restraint effect; In the stretching stage, the development of intercrystalline cracks is the main cause of AE signals in tensile stage, and AE signal followed hysteresis phenomenon. (3) Comparing with impurity salt rock, the cumulative ringing counts of the four compression loading and unloading stages are 3.13 times higher than impurity salt rock, AE signal of pure salt rock is weaker during tension loading and unloading, the cumulative ringing count increases slightly, a large number of acoustic emission signals accompany only the final tensile failure process. Under the condition of tension-compression alternating, AE signals of pure salt rock with the same tensile or compressive stress levels are more active than those of impurity salt rock, and the number of AE events in compression stage is larger than that in tension stage.